Topical issues of Pedagogy of Theatrical Art - Umarov M.B (Research Parks Publishers, 2021)
This article is devoted to the problems of proper upbringing of the sense of imitation, stamp and creativity, which is a topical issue of three scholars - Plato, Aristotle and Stanislavsky theatrical art yesterday and today. In the article, Plato's views on the art of performance and its evaluation in the book